TEKNOLOGI TEPAT GUNA PENERAPAN HYDROCOOLING DAN PENYIMPANAN DINGIN UNTUK MEMPERPANJANG UMUR SIMPAN BUAH DAN SAYUR YANG TERKENA ERUPSI GUNUNG SINABUNG - Maya Sari; Roida Ervina Sinaga; Juliana Br Simbolon; Robert Sinaga (JURNAL AGROTEKNOSAINS, 2019)
The effect of Mt. Sinabung eruption has profoundly affected the quality of fruit and vegetable production, in this context is fruit and vegetables. Fruit and vegetable, carrot, strawberry and pakcoy is kind of fruit and vegetable that is consumed by the community especially the communities surrounding both the mountain ranges and the general medan area. The fruit and vegetable are kinds of climateric and the lifespan must be kept. During the transportation of field to market, there wa both mechanical and physical damage.The damage will obviously harm farmers, merchants, and other marketers. So that hydrocooling is applied as a post harvest treatment. Hydrocooling is done right after the harvest, This prosess extracts heat from fruit and vegetables so that respiration and transpiration can continue for a long time.The lack of farmer understanding for post harvest handling is a major problem. Therefore, farmers in aberastagi will be given education and training about post harvest handling (hydrocooling) so they could understand and self applying that will keep their produce fresh. As for the output of this activity is a simple hydrocooling device designed as a visual aid in training. This hydrocooling equipment can also be a reference to training science for schoolchildren in particular agriculture schools and could be a referenceto researchers and developing them.